Implementasi Rancangan Web Desa Botutonuo Sebagai Upaya Menuju Desa Sejahtera Dan Mandiri Di Kawasan Teluk Tomini - Tri Handayani Amaliah (Institut Nalanda, 2023)
Botutonuo Village is located on the northern coast and southern part of the sea, Bone Bolango Regency. 70% of the population in Botutonuo Village have a livelihood as farmers/planters who have the same amount of marine products and plantations. However, in terms of the utilization of natural resources, what stands out the most in Botutonuo Village is the coconut plantation (annual crop) which yields thousands of tonnes per harvest. The rapid development of technology today certainly plays an important role for human life in the dissemination of information. The reality is that Botutonuo Village has abundant natural resources besides tourism potential but is not yet known by the wider community. Web Desa is not only able to publish information about Botutonuo Village but also as a means of promoting its potentials. This community service is a facilitator in creating as well as implementing the Botutonuo Village Web in order to create a prosperous village through the utilization and development of its potentials. This community service activity from the Gorontalo State University Accounting Study Program helps develop and guide the management of the village web that has been made. Through the village website, it is hoped that it can help the village government provide services to the community as well as a means of publishing information about the village and its potential.